Improvement of Seedling Establishment and Lodging Resistance in Selected Rice Cultivars Using Growth Regulators - Sri Wahyuni (2002)
Studies were conducted to investigate the possible use of growth regulators to improve seedling establishment and lodging resistance in wet seeded rice cultivars. The first experiment was designed to evaluate the effect of growth regulators i.e. GA3 and IBA as seed treatment on seedling establishment, growth and grain yield. Levels of GA3 were 25, 50 and 100 mg/L and IBA were 10, 20 and 40 mg/L; and water was used as control. The treatments were tested on four rice cultivars i.e. Membramo and Widas (Indonesian cultivars), MR 219 and MR 84 (Malaysian cultivars). In the second experiment, growth retardants paclobutrazol and prohexadione calcium at 50, 100 and 200 mg/L as foliar application at panicle initiation were investigated for their effects on growth, lodging resistance and yield of four rice cultivars. A third experiment was conducted to evaluate selected combinations of seed treatment and foliar spray on growth, lodging resistance and yield of two rice cultivars. Results of the study showed that GA3 as seed treatment induced favourable early emergence but shoot etiolation resulted in seedlings more prone to lodging during the vegetative phase. On the other hand, IBA treatments improved root growth by increasing the number of adventitious roots and contributed towards better establishment with seedlings having broader and greener leaves. IBA at all concentrations did not show any significant differences in all growth parameters measured and had no detrimental effects on grain yield. IBA at 10 mg/L was sufficient in providing the required improvement in the rice seedlings. Cultivar response to GA3 was similar, however response to IBA was different. Indonesian cultivars had shoot lengths comparable to the control, while the Malaysian cultivars had shorter shoots. Foliar applied growth retardants inhibited plant growth, retarded internode and culm length but increased culm diameter. All treated plants had higher bending and stem breaking resistance compared to the control. The treatments also improved culm thickness, increased the amount of cellulose, hemicellulose and lignin content in culms. Histological studies showed greater compaction of parenchyma cells and thickening of parenchyma cell walls. The higher bending and breaking resistance and hence improved lodging resistance was largely attributed to these changes in culms treated with the growth retardants.